First Report on the Asexual Morphology of Nigrograna jinghongensis (Nigrogranaceae, Pleosporales) with a New Host Record from China - Li‐Xue Mi; Hai‐Yan Song; Kevin D. Hyde; Prapassorn D. Eungwanichayapant; Ausana Mapook; Mu‐Sen Chen; Dian‐Ming Hu (New Zealand Journal of Botany, 2026)
Nigrograna jinghongensis was originally described based on sexual morphology from decaying woody litter in Yunnan Province, China. In this study, we report its asexual morph, isolated as endophytes from Tetradium ruticarpum in Anhui Province. The asexual morph of N. jinghongensis features coelomycetous pycnidia that are dark brown and globose to pyriform, bearing filiform, septate conidiophores with phialidic, hyaline conidiogenous cells, and ellipsoidal to subcylindrical, aseptate, guttulate conidia. Species identification was confirmed by multigene phylogenetic analysis using ITS, LSU, SSU, tef1‐α , and rpb2 sequences. This is the first report of the asexual morph of N. jinghongensis , expanding knowledge of its life cycle, ecological adaptability, and host association.

Mycotoxin deoxynivalenol drives antibiotic resistance evolution in Bacillus cereus via cell wall remodeling, compromising clinically critical antibiotics - Fengru Deng; Linyu Ke; Mi Huang; Meichan Chen; Zhongsong Chen; Peiqiang Mu; Mengzhuo Shi; Jun Wu; Yiqun Deng (Journal of Hazardous Materials, 2026)

Numerical simulation on creep behavior of argillaceous siltstone under compression-shear coupling and humidity variations - Jiajun Ran; Bo Hu; Qiaohai Tan; Xianghe Ye; Yugang Cheng; Zhiqiang Lv; Mostafa Sharifzadeh; Mi Nie; Jian Mu; Wenbin Guo (Ocean Engineering, 2025)

Evaluation of mechanical properties and geological features of highly sandy dolomite: consequences for engineering safety - Meiqian Wang; Wei Xu; Hongzhong Xu; Hongyuan Mu; Jian Mi; Yonghong Wu; Yangxing Wang; Baofa Cai (Bulletin of Engineering Geology and the Environment, 2025)
The Central Yunnan Water Diversion Project (CYWD Project) is a crucial water source initiative within Yunnan’s revitalization strategy. However, significant engineering challenges arise, such as tunnel mud and water inrush due to the presence of highly sandy dolomite. Therefore, understanding the mechanical properties of this dolomite is essential for ensuring safe construction in the tunnel engineering of the CYWD Project. This paper examines the highly sandy dolomite found in the Sinian strata of Zbdn and Zbd, located along the Yuxi section of the tunnel line, using both micro and macro testing methods. Microscopic analyses, including slice identification, CT scanning, and scanning electron microscopy, were conducted to determine the primary geological characteristics and classification standards of the sandy dolomite. Additionally, macro tests, such as in-situ needle penetration tests (NPT), uniaxial compressive strength tests (UCS), and shear tests, were performed. Using the least squares method and regression analysis, relationships between the needle penetration index (NPI), UCS, and shear strength were established. This study established reliable relationships between the needle penetration index, uniaxial compressive strength, and shear strength parameters of highly sandy dolomite encountered in the CYWD Project. The geological features were also characterized using macro- and micro-scale testing, providing a theoretical basis for the project’s design and safety. This conversion relationship offers a theoretical basis for the design, construction, and safety evaluation of the CYWD Project. The parameters developed are sufficiently reliable for evaluating engineering in areas with highly sandy dolomite. Graphical abstract

Salicylic acid nanoliposomes treatment alleviates chilling injury in postharvest baby ginger by regulating membrane lipid metabolism - Zhenzhen Mi; Honglei Mu; Yanchao Han; Ruiling Liu; Ben Niu; Guannan Wang; Huizhi Chen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

TRPV1-targeted ion-responsive hydrogel against pyroptosis of dry eye disease - Xiangyu Ding; Jingqing Mu; Baoyue Mi; Zhengxi Yuan; Xiaolong Fang; Xiaoyuan Ji; Xiaoyong Yuan; Shutao Guo; Xia Hua (Chemical Engineering Journal, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

TAG encodes an adenine nucleotide transport protein that regulates leaf color in rice - Xinfang Zhang; Wenwen Xiao; Mi Wei; Ruhui Wu; Jinyan Liu; Jing You; Jianyan Mu; Jichao Zhang; Yanling Yang; Yitao Wan; Yinghua Lin; Guanghua He; et al. (Euphytica, 2024)

Clinical outcomes and immunological features of COVID-19 patients receiving B-cell depletion therapy during the Omicron era - Chan Mi Lee; Minji Kim; Seong-wook Park; Chang Kyung Kang; Pyoeng Gyun Choe; Nam Joong Kim; Hyeon Jae Jo; Hyun Mu Shin; Chang-Han Lee; Hang-Rae Kim; Wan Beom Park; Myoung-don Oh (Infectious Diseases, 2024)

Study on the differences of metabolites and their bioactivities of Lithocarpus under different processing methods - Wenhuan Lou; Xi Mu; Jiajia Liu; Mi Xun; Yunyang Hu (Food Bioscience, 2023)

Effects of slow- and controlled-release nitrogen fertilizers on bacterial and fungal community composition in a double-cropping rice system - Yan Sun; Jian Wang; Wentian Mi; Weiyi Mu; Wanghai Tao; Chao Chen; Wenhai Mi; Lijun Su (Soil and Tillage Research, 2023)

Effects of Irrigation Using Activated Brackish Water on the Bacterial Community Structure of Rhizosphere Soil - Yan Sun; Chunhong Wang; Wentian Mi; Zhi Qu; Weiyi Mu; Jian Wang; Jihong Zhang; Quanjiu Wang (Journal of Soil Science and Plant Nutrition, 2022)
The technology for the activation of irrigation brackish water was successful at improving the soil environment and crop yields. However, very few studies have examined how activated brackish water irrigation affects the rhizosphere bacterial communities and network patterns. By combining 16S rRNA high-throughput sequencing, we evaluated the diversity and composition of the rhizosphere bacterial community after being subjected to different types of irrigation with activated brackish water. We also analyzed the correlation and co-occurrence networks among the bacterial diversity, composition, and rhizosphere soil properties. The results showed that compared with brackish water irrigation, the salt content of activated irrigation water significantly decreased by 9.35%, 9.83%, and 12.95%, respectively. Irrigation with different types of activated brackish water had no significant ( p > 0.05) effect on the diversity of the rhizosphere bacterial community, but it significantly changed its community composition, which was primarily dominated by soil nutrient indicators. The soil total nitrogen (TN) showed a significant ( p < 0.01) negative correlation with the Chao1 index. Additionally, the changes in bacterial communities under different types of activated brackish irrigation water mainly occurred at the genus level. We showed that the rhizosphere soil that had been irrigated with oxygenated brackish water and magnetized brackish water better supported the reproduction of some soil-borne pathogens. Magnetization-oxygenation coupling treatment could significantly reduce the colonization of soil-borne pathogens of the rhizosphere soil, while also favoring the function of functional bacteria involved in soil nutrient transformation. This study highlights the main factors affecting the rhizosphere soil bacterial community structure by activated brackish water irrigation, while also providing new technical support for brackish water irrigation.

Clinical characteristics of re-hospitalized COVID-19 patients with recurrent positive SARS-CoV-2 RNA: a retrospective study - Lei Pan; Runsheng Wang; Na Yu; Chao Hu; Junhong Yan; Xiaomin Zhang; Tao Wang; Jungui Hao; Fuquan Gao; Tonggang Liu; Jing Wang; Xiaojing Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

A core set of microsatellite loci for yellow-throated marten, Martes flavigula: a case of inferences of family relationships - Seon-Mi Lee; Hea Chang Moon; Hye Sook Jeon; Eui-Geun Song; Donggul Woo; Junghwa An; Mu-Yeong Lee (Genes & Genomics, 2019)

Optimal precursors of double-gyre regime transitions with an adjoint-free method - Shijin Yuan; Mi Li; Qiang Wang; Kun Zhang; Huazhen Zhang; Bin Mu (Journal of Oceanology and Limnology, 2019)

CNOP-P-based parameter sensitivity for double-gyre variation in ROMS with simulated annealing algorithm - Shijin Yuan; Huazhen Zhang; Mi Li; Bin Mu (Journal of Oceanology and Limnology, 2019)

A 90-Day Repeated Oral Dose Toxicity Study of Alismatis Rhizoma Aqueous Extract in Rats - Mu-Jin Lee; Ho-Kyung Jung; Ki-Ho Lee; Ji-Hun Jang; Mi-Ok Sim; Tea-Gyeong Seong; Byung-Kwan Ahn; Jin-Han Shon; Seong-Ho Ham; Hyun-Woo Cho; Yong-Min Kim; Sung-Jin Park; et al. (Toxicological Research, 2019)

Genetic diversity and population demography of narrow‐ridged finless porpoises from South Korea on the basis of mitochondrial DNA variation: Implications for its conservation in East Asia - Seon‐Mi Lee; Kyum Joon Park; Byung‐Yeob Kim; Mi‐Sook Min; Hang Lee; Mu‐Yeong Lee (Marine Mammal Science, 2019)
The narrow‐ridged finless porpoise, Neophocaena asiaeorientalis , is a small cetacean inhabiting the coastal waters of Taiwan, East China, Korea, and Japan, and is threatened by anthropogenic pressures. We analyzed the mitochondrial control region of N. asiaeorientalis from Korean waters to better understand the genetic diversity, population structure, and demographic history through comparison with previously reported sequences from Japan and China. The network and phylogenetic analyses illustrated that few common haplotypes were centrally located, and that most of the unique haplotypes were on the edges of the branches. Moreover, the estimates of fixation indices and gene flow revealed significant genetic differentiation among the regions in East Asia. The mismatch distribution suggested a population expansion in the late Pleistocene. We propose that the current genetic variation in N. asiaeorientalis in East Asia was shaped by historical demographic expansion during the late Pleistocene. The N. asiaeorientalis of Korean waters has the highest diversity observed with the sampling available at this time. However, the abundance of N. asiaeorientalis in Korean waters has rapidly declined and the species needs protection from bycatch.

Anti-allergic inflammatory effect of vanillic acid through regulating thymic stromal lymphopoietin secretion from activated mast cells - Hyun-Ja Jeong; Sun-Young Nam; Hee-Yun Kim; Mu Hyun Jin; Mi Hye Kim; Seok Seon Roh; Hyung-Min Kim (Natural Product Research, 2018)

Beneficial Effects of Cynaroside on Cisplatin-Induced Kidney Injury In Vitro and In Vivo - Jong-Hyun Nho; Ho-Kyung Jung; Mu-Jin Lee; Ji-Hun Jang; Mi-Ok Sim; Da-Eun Jeong; Hyun-Woo Cho; Jong-Choon Kim (Toxicological Research, 2018)

Phylogeography of the Asian lesser white-toothed shrew, Crocidura shantungensis, in East Asia: role of the Korean Peninsula as refugium for small mammals - Seo-Jin Lee; Mu-Yeong Lee; Liang-Kong Lin; Y. Kirk Lin; Yuchun Li; E-Hyun Shin; Sang-Hoon Han; Mi-Sook Min; Hang Lee; Kyung Seok Kim (Genetica, 2018)

An Inframe Trinucleotide Deletion in MTRR Exon 1 is Associated with the Risk of Spina Bifida - Jun Zhang; Xiao-lu Dai; Gui-cen Liu; Juan Wang; Xue-yi Ren; Mu-hua Jin; Nan-nan Mi; Shu-qin Wang (NeuroMolecular Medicine, 2017)

Trend of blood lead, mercury, and cadmium levels in Korean population: data analysis of the Korea National Health and Nutrition Examination Survey - Jeong-Wook Seo; Byoung-Gwon Kim; Yu-Mi Kim; Rock-Bum Kim; Jin-Yong Chung; Kyoung-Mu Lee; Young-Seoub Hong (Environmental Monitoring and Assessment, 2015)

Resveratrol relieves hydrogen peroxide-induced premature senescence associated with SIRT1 in human mesenchymal stem cells - Mi Ran Choi; Dal Mu Ri Han; Sun Hwa Kim; Takbum Ohn; Kyoung Hwa Jung; Young Gyu Chai (Molecular & Cellular Toxicology, 2014)